2016
DOI: 10.3389/fpls.2016.01702
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the Whitefly Bemisia tabaci Cyclophilin B Protein in the Transmission of Tomato yellow leaf curl virus

Abstract: Tomato yellow leaf curl virus (TYLCV) is a single-stranded (ssDNA) begomoviruses that causes severe damage to tomato and several other crops worldwide. TYLCV is exclusively transmitted by the sweetpotato whitefly, Bemisia tabaci in a persistent circulative and propagative manner. Previous studies have shown that the transmission, retention, and circulation of TYLCV in its vector involves interaction with insect and endosymbiont proteins, which aid in the transmission of the virus, or have a protective role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…However, contrary to cotton plants infected with silenced Hsp20, Hsp40, Hsp70, and k -1 whitefly which showed increased viral load, the plants infected with CYCP silenced whiteflies contained lower number of viral transcripts then the untreated plants ( Figure 7E). The obtained results are consistent with previous reports in which knockdown of cyclophilin (CYCP) in B. tabaci showed lower efficiency to transmit tomato leaf curl virus (Kanakala and Ghanim, 2016;Kanakala et al, 2019).…”
Section: Knockdown Of Osmoregulatory Genessupporting
confidence: 92%
See 1 more Smart Citation
“…However, contrary to cotton plants infected with silenced Hsp20, Hsp40, Hsp70, and k -1 whitefly which showed increased viral load, the plants infected with CYCP silenced whiteflies contained lower number of viral transcripts then the untreated plants ( Figure 7E). The obtained results are consistent with previous reports in which knockdown of cyclophilin (CYCP) in B. tabaci showed lower efficiency to transmit tomato leaf curl virus (Kanakala and Ghanim, 2016;Kanakala et al, 2019).…”
Section: Knockdown Of Osmoregulatory Genessupporting
confidence: 92%
“…The target gene sequences were pulled out from whitefly genome database 1 . Selection of genes was done on the basis of their functional role i.e., osmoregulation (Aquaporin (AQP) (Benoit et al, 2014), Calcitonin (CAL) (Furuya et al, 2000;Cohen, 2012;Zandawala, 2012), virus transmission (Cyclophilin B (CYCP) (Kanakala and Ghanim, 2016), Knottin (k-1) (Hariton Shalev et al, 2016), Heat shock proteins i.e., Hsp20, Hsp40 and Hsp70 (Gotz et al, 2012;Gorovits and Czosnek, 2017) and other genes associated with vital processes i.e., SNF7 (SWItch/Sucrose Non-Fermentable) and IAP (inhibitor of apoptosis) (Blitvich et al, 2002). The expression of these genes was validated using gene specific primers (designed using Primer3 software) ( Table 1) in qRT-PCR performed using LightCycler R 96 System (Roche life sciences, Mannheim, German) with SYBR-Green detection (SYBR R Premix Ex TaqTMII, Takara).…”
Section: In Vitro Dsrna Synthesismentioning
confidence: 99%
“…CP immunolocalization has shown that TYLCVs concentrate in the digestive tract, especially the midgut and the filter chamber ( Figure 1 ,7,V) [ 56 , 57 , 58 ]. Other begomoviruses, such as the bipartite WmCSV, also concentrate in the midgut [ 57 ].…”
Section: Organs Tissues and Cells Visited By Begomoviruses Circulmentioning
confidence: 99%
“…From the three B. tabaci peptidyl-prolyl isomerases protein genes (PPIases or cyclophilins Cyps) CypB , CypD and CypG , only the expression of CypB was upregulated by two-fold in viruliferous B. tabaci B. CypB and TYLCV CP formed complexes that could be resolved in vitro [ 58 ]. In addition, CypB and TYLCV CP co-localized in the filter chamber, cecae and midgut indicated that these interactions may mediate virus translocation in the haemolymph.…”
Section: Organs Tissues and Cells Visited By Begomoviruses Circulmentioning
confidence: 99%
“…One of the most economically important begomoviruses transmitted by B. tabaci is tomato yellow leaf curl virus (TYLCV) [ 9 ], which has been the focus of numerous studies to better understand protein interactions between whiteflies and begomoviruses [ 10 , 11 , 12 ]. Transcriptome profiling has also been used to help understand the molecular mechanism of the whitefly–begomovirus relationship, including whitefly transcriptome responses to acquiring TYLCV [ 13 , 14 , 15 ] and tomato yellow leaf curl China virus (TYLCCNV) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%